Effect Analysis of CAR, BOPO, NPL, ROA, and Total Assets on LDR at Bank DKI (Period of 2014 – 2018) - Yuda Adipraya Iskandar; Erric Wijaya (Jurnal Ilmu Manajemen dan Ekonomika, 2021)
Managing liquidity at a bank as an intermediary institution, is very important. Liquidity itself is considered as a reflection of the trust of customers or investors to bank. By knowing the factors that affect liquidity, banks are able to manage liquidity better. This study aims to analyze the variables that affect liquidity which is proxied by Loan to Deposit Ratio (LDR) at Bank DKI. The independent variables used are Capi-tal Adequacy Ratio (CAR), Operating Expenses on Operating Income (BOPO), Non Performing Loans (NPL), Return On Assets (ROA), and Total Assets. The data was obtained from secondary data from fi-nancial statements issued by Bank DKI in the period January 2014 to December 2018. The sampling tech-nique used purposive sampling. The hypothesis in this study is based on previous research and various oth-er supporting theories which are then analyzed using multiple linear regression analysis with Eviews 9. The results of this study indicate that CAR and NPL have a positive effect on LDR, Total Assets negative-ly affect LDR, ROA has no effect on LDR while BOPO cannot be used because of multicollinearity.